c.1 - "Salmen, Lawrence F." (New York, 1989)
Listen to the People is an account of the author's experience living among the poor inhabitants of World Bank urban development projects in La Paz, Bolivia, and Guayaquil, Ecuador. By viewing slum upgrading and new housing through the eyes of the people who lived there, he was able to explain some of the projects' failings and to identify some of their unexpected benefits. By sharing the lives of slum dwellers he came to understand the frustrations and hard economic reality of their existence and gained insight into needs that were not apparent to an outsider. The book testifies to the effective ness with which anthropological techniques of participant observation can be applied in the context of economic development.
Keywords: Economic development projects-Bbolivia -La -Paz-Evaluati